The Genetic Diversity of Enset (Ensete ventricosum) Landraces Used in Traditional Medicine Is Similar to the Diversity Found in Non-medicinal Landraces - Nuraga, Gizachew Woldesenbet; Feyissa, Tileye; Tesfaye, Kassahun; Biswas, Manosh Kumar; Schwarzacher, Trude; Borrell, James S.; Wilkin, Paul; Demissew, Sebsebe; Tadele, Zerihun; Heslop-Harrison, J. S. (Pat) (Frontiers in Plant Science, 2022)
Enset (Ensete ventricosum) is a multipurpose crop extensively cultivated in the southern and southwestern Ethiopia for human food, animal feed and fiber. It has immense contributions to the food security and rural livelihoods of 20 million people. Several distinct enset landraces are cultivated for their uses in traditional medicine. These landraces are vulnerable to various human-related activities and environmental constraints. The genetic diversity among the landraces is not verified to plan conservation strategy. Moreover, it is currently unknown whether medicinal landraces are genetically differentiated from other landraces. Here, we characterize the genetic diversity of medicinal enset landraces to support effective conservation and utilization of their diversity. We evaluated the genetic diversity of 51 enset landraces, of which 38 have reported medicinal value. A total of 38 alleles across the 15 SSR loci, and moderate level of genetic diversity (He = 0.47) were detected. AMOVA revealed that only 2.4% of the total genetic variation was contributed by variation among medicinal and non-medicinal group of landraces, with an FST of 0.024. A neighbor-joining tree showed four separate clusters with no correlation to the use values of the landraces. Except two, all ‘medicinal’ landraces with distinct vernacular names were found to be genetically different, showing that vernacular names are good indicator of genetic distinctiveness in these specific groups of landraces. Discriminant Analysis of Principal components also confirmed the absence of distinct clustering between the two groups. We found that enset landraces were clustered irrespective of their use value, showing no evidence for genetic differentiation between enset grown for ‘medicinal’ uses and non-medicinal landraces. This suggests that enset medicinal properties may be restricted to a more limited number of genotypes, might have resulted from the interaction of genotype with the environment or management practice, or partly misreported. The study provide baseline information that promotes further investigations in exploiting the medicinal value of these specific landraces